The productivity effects of worker replacement in young firms - Martin Murmann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Existing management research has so far dealt with the consequences of labor turnover for established firms, but has not addressed its effect on young entrepreneurial businesses. In this paper I assess, both theoretically and empirically, the productivity effects of worker replacement in young firms. Worker replacement isolates labor turnover due to employee replacement as a separate category of turnover and has been shown to positively affect the productivity of established firms in previous research. Using a large and representative sample of German start-ups, I show that worker replacement has negative effects on young firms' productivity that remain even when controlling for moderating factors. These effects are even more negative when the founder does not have prior managerial experience.
urn:nbn:de:bsz:180-madoc-421195
Keywords: L26; M13; J24; J63; D22; 330; Firm productivity; Labour turnover; Churning; Entrepreneurship